Self-Efficacy, Resilience and Distress: Challenges in Education for Sustainable Entrepreneurship in a Health Context - Couto, I. (2022)
The European Commission has highlighted the development of entrepreneurship competence in lifelong learning skills. In this way, the present study aims to contribute towards fostering the intrapreneurial mindset in healthcare settings. The focus of attention is on the relationship between organizational structures and processes (work-related content and content, specifically psychosocial risk factors), as well as individual wellbeing factors (distress and resilient coping) that could be relevant not only for the promotion of organizational wellbeing, but also to ensure an intrapreneurship-friendly environment (through the promotion of self-efficacy). An empirical study was conducted involving 333 formal caregivers of healthcare services. Portuguese versions of the instruments Kessler Psychological Distress Scale (K10), Brief Resilient Coping Scale (BRCS), and Copenhagen Psychosocial Questionnaire (COPSOQ III, medium version) were employed. Results show that resilience and distress (at the individual level), as well as role clarity, control over working time, and job insecurity (at the organizational level) are predisposing factors for self-efficacy, which are highlighted as essential to ensure an enabling environment for intrapreneurship and wellbeing. For practical consideration, we present an entrepreneurial mindset development strategy through the implementation of cause-related marketing as a pedagogical tool for entrepreneurship within the organization, which allows for experimentation and the necessary creative flexibility